2009
DOI: 10.1080/01425690903235292
|View full text |Cite
|
Sign up to set email alerts
|

Planning mobile futures: the border artistry of International Baccalaureate Diploma choosers

Abstract: This paper reports on a study of students choosing the International Baccalaureate (IB) Diploma over state-based curricula in Australian schools. The IB Diploma was initially designed as a matriculation certificate to facilitate international mobility. While first envisaged as a lifestyle agenda for cultural elites, such mobility is now widespread with more people living 'beyond the nation' through choice or circumstance. Beck and others highlight how the capacity to cross national borders offers a competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…This revealed that 7% said their socioeconomic status was 'high' whilst 80% were 'middle income'. It has been asserted in an Australian context (Doherty, Mu, and Shield 2009) that IB graduates there are utilizing their capacity to cross national borders (termed 'border artistry') and how the IB offers them a competitive edge with which to strategically pursue economic and cultural capital. Congleton (1989) remarked on such 'artistry' as 'status-seeking games', where an individual's utility is determined by his/ her relative expenditure on status-seeking activities rather than by absolute consumption.…”
Section: The Individualisation Of Societymentioning
confidence: 99%
“…This revealed that 7% said their socioeconomic status was 'high' whilst 80% were 'middle income'. It has been asserted in an Australian context (Doherty, Mu, and Shield 2009) that IB graduates there are utilizing their capacity to cross national borders (termed 'border artistry') and how the IB offers them a competitive edge with which to strategically pursue economic and cultural capital. Congleton (1989) remarked on such 'artistry' as 'status-seeking games', where an individual's utility is determined by his/ her relative expenditure on status-seeking activities rather than by absolute consumption.…”
Section: The Individualisation Of Societymentioning
confidence: 99%
“…Along the same lines, scholars outside of the United States have critiqued IB for primarily serving elite student populations, arguing that schools, parents, and children use IB as a means for gaining and reproducing advantage in unequal educational settings (Bunnell, 2008;Doherty, 2012;Doherty, Mu, & Shield, 2009;Tarc, 2009).…”
Section: Guiding Researchmentioning
confidence: 99%
“…There is a small but growing literature documenting IB programs from a variety of theoretical orientations, both celebratory and critical. It considers the origins, philosophy and orientations of its internationalised curriculum (Cambridge, 2010; Conner, 2009; Hill, 2002; Van Oord, 2007); its global distribution (Bagnall, 2005; Bunnell, 2008; Halicioglu, 2008; Poonoosamy, 2010); the student experience (Payne, 2005); the dispositional outcomes for students (Doherty, Mu, & Shield, 2009; Hayden & Wong, 1997; Heyward, 2002; Resnick, 2009); assessment practices (Allen & Readman, 2009; Lowe, 2000); its marketing (Doherty, 2009; MacDonald, 2006); and choice rationales (MacKenzie, Hayden, & Thompson, 2003; Paris, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%